Effect of shallow, rotary cultivation with vertical tines and nitrogen fertilization on the seed productivity of creeping red fescue - Fairey, N. A.; Lefkovitch, L. P. (Canadian Journal of Plant Science, 2002)
A field study in the Peace River region of north-western Canada evaluated the effect of shallow rotary cultivation with vertical tines on the seed production of stands of creeping red fescue (Festuca rubra L. var. rubra). At four sites, rotary cultivation treatments (None, Low, Medium and High tine rotor speed) were applied after the harvest of the first and second seed crops, in factorial combination with the time of application of 68 kg ha -1 N fertilizer (Early fall, Late fall, and Split 1:1 early:late fall). In harvest years 2 and 3, the effect of site on seed yield per unit land area was modified by both N and rotary cultivation. In harvest year 2, seed yield at Site 1 was increased greatly by rotary cultivation, regardless of the tine rotor speed, but there was little difference among the four cultivation treatments at the other three sites. In harvest year 3, seed yield was increased with Low, Medium and High rotary cultivation to 6- to 11-fold that without rotary cultivation at Sites 1 and 2 but only to 1.4- to 2-fold at Sites 3 and 4. Seed yield response to rotary cultivation was dependent on site and year, a reflection of the physiological status of the fescue plants at each specific site. Rotary cultivation treatments may have been too detrimental to tiller growth and development for sustaining and enhancing seed yield, particularly at Sites 3 and 4 prior to harvest year 2. There was no consistent pattern of response in seed yield among the four sites to the three N treatments in either harvest year 2 or 3. Although there was a significant (P < 0.001) N × rotary cultivation interaction for seed yield in harvest year 3, the pattern among cultivation treatments was generally similar for each N treatment; compared to no cultivation, the three cultivation treatments more than doubled seed yield to 255–322 kg ha -1 with Early and Split N and increased it 4- to 6-fold to 203–288 kg ha -1 with Late N. There is some potential for rotary cultivation, but the selected treatments were generally too ...